2002
DOI: 10.1126/science.1075333
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Signaling and Plasticity Mechanisms

Abstract: In excitatory synapses of the brain, specific receptors in the postsynaptic membrane lie ready to respond to the release of the neurotransmitter glutamate from the presynaptic terminal. Upon stimulation, these glutamate receptors activate multiple biochemical pathways that transduce signals into the postsynaptic neuron. Different kinds of synaptic activity elicit different patterns of postsynaptic signals that lead to short- or long-lasting strengthening or weakening of synaptic transmission. The complex molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
504
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 658 publications
(521 citation statements)
references
References 86 publications
9
504
0
8
Order By: Relevance
“…In the CNS, NMDAR-mediated signals are critical for the survival of developing neurons and for several forms of synaptic plasticity and learning and memory (Sheng and Kim, 2002). Conversely, NMDAR-mediated excitotoxicity has been implicated in a diversity of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, NMDAR-mediated signals are critical for the survival of developing neurons and for several forms of synaptic plasticity and learning and memory (Sheng and Kim, 2002). Conversely, NMDAR-mediated excitotoxicity has been implicated in a diversity of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The major postsynaptic glutamate receptors include the N-methyl-D-aspartate receptor (NMDAR), the α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor (AMPAR), and the group I metabotropic glutamate receptor (mGluR). It has been reported that PSD-70 as Src, a member of the Src family in the central nervous system (CNS), which plays important roles in the synaptic targeting and signaling of NMDARs [4,5] . However, the mechanisms remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Postsynaptic density (PSD) proteins are necessary for excitatory glutamatergic postsynaptic responses, and include scaffolding and functional elements that modulate/mediate signal transduction and trafficking of synaptic proteins (reviewed by Sheng and Kim, 2002;Wenthold et al, 2003;Bredt and Nicoll, 2003;Ehrengruber et al, 2004). In addition to glutamate receptors (GluRs) such as α-amino-3-hydroxy-5-methyl-4-isoxazoleproprionic acid (AMPA) and Nmethyl-D-aspartate (NMDA) receptors, numerous other proteins associate with GluRs in the postsynaptic membrane and PSD.…”
Section: Introductionmentioning
confidence: 99%